Iron Supply via NCOA4-Mediated Ferritin Degradation Maintains Mitochondrial Functions - Fujimaki, Motoki (Mol Cell Biol, 2019)
Iron is an essential nutrient for mitochondrial metabolic processes, including mitochondrial respiration. Ferritin complexes store excess iron and protect cells from iron toxicity. Therefore, iron stored in the ferritin complex might be utilized under iron-depleted conditions. In this study, we show that the inhibition of lysosome-dependent protein degradation by bafilomycin A1 and the knockdown of NCOA4, an autophagic receptor for ferritin, reduced mitochondrial respiration, respiratory chain complex assembly, and membrane potential under iron-sufficient conditions. However, autophagy did not contribute to degradation of the ferritin complex under iron-sufficient conditions. Knockout of the ferritin light chain, a subunit of the ferritin complex, inhibited ferritin degradation by decreasing interactions with NCOA4. However, ferritin light chain knockout did not affect mitochondrial functions under iron-sufficient conditions, and ferritin light chain knockout cells showed a rapid reduction of mitochondrial functions compared with wild-type cells under iron-depleted conditions. These results indicate that the constitutive degradation of the ferritin complex contributes to the maintenance of mitochondrial functions.